Development, characterization, and cross-species/genera transferability of SSR markers for rubber tree (Hevea brasiliensis) - Yu Fei; Feng Su-Ping; Li Wei-Guo; Wang Bao-Hua; Wang Jing-Yi; Wu Yao-Ting (Plant Cell Reports, 2011)
Genomic simple sequence repeat (SSR) markers are particularly valuable in studies of genetic diversity, evolution, genetic linkage map construction, quantitative trait loci tagging, and marker-assisted selection because of their multi-allelic nature, reproducibility, co-dominant inheretance, high abundance, and extensive genome coverage. The traditional methods of SSR marker development, such as genomic-SSR hybrid screening and microsatellite enrichment, have the disadvantages of high cost and complex operation. The selectively amplified microsatellite method is less costly and highly efficient as well as being simple and convenient. In this study, 252 sequences with SSRs were clones from the rubber tree (Hevea brasiliensis) genome from which 258 SSR loci were obtained. The average repeat number was six. There were only 10 (3.9;) mononucleotide, trinucleotide, and pentanucleotide repeats, whereas the remaining 248 (96.1;) were dinucleotide repeats, including 128 (49.6;) GT/CA repeats, 118 (45.7;) GA/CT repeats, and 2 (0.8;) AT/TA repeats. A total of 126 primer pairs (see ESM) were successfully designed of which 36 primer pairs generated polymorphic products from 12 accessions of the cultivated species, 4 related species, and 3 species of the family Euphorbiaceae. In addition, investigations based on four genomic SSRs (GAR4, ACR22, CTR25, and GTR28) by cloning and sequencing provided evidence for cross-species/genera applicability, and homologous sequences were obtained from the rubber tree and Euphorbiaceae. Further analysis about the variation of the flanking regions of the four markers was carried out.
Keywords: Development; Flanking regions; Genomic SSR; Polymorphism; Variation